\[\boxed{\text{876\ (876).\ }\text{Еуроки\ -\ ДЗ\ без\ мороки}}\]
\[f(x) = 4x - 3\ \ \ и\ \ \ \]
\[g(x) = 3x - 2\]
\[4x - 3 = 3x - 2\ \ \]
\[x = 1\ \ \]
\[f(1) = 1\]
\[x\] | \[0\] | \[1\] |
---|---|---|
\[y\] | \[- 3\] | \[1\] |
\[x\] | \[0\] | \[1\] |
---|---|---|
\[y\] | \[- 2\] | \[1\] |
\[1)\ f(x) > g(x)\ при\ x > 1;\ \ \]
\[2)\ f(x) < g(x)\ при\ \ x < 1.\]
\[\boxed{\text{876.\ }\text{Еуроки\ -\ ДЗ\ без\ мороки}}\]
\[x + y = 6;\ \ \ \ \ \text{xy} = - 3\]
\[1)\ x³y² + x²y³ =\]
\[= x^{2}y^{2}(x + y) = ( - 3)^{2} \cdot 6 =\]
\[= 9 \cdot 6 = 54\]
\[2)\ (x - y)^{2} = x² - 2xy + y^{2} =\]
\[= x^{2} + 2yx + y^{2} - 4xy =\]
\[= (x + y)^{2} - 4xy =\]
\[= 6^{2} - 4 \cdot ( - 3) = 36 + 12 = 48\]
\[3)\ x^{4} + y^{4} =\]
\[= x^{4} + y^{4} + 2x^{2}y^{2} - 2x^{2}y^{2} =\]
\[= \left( x^{2} + y^{2} \right)^{2} - 2x^{2}y^{2} =\]
\[= \left( x^{2} + y^{2} \right)^{2} - 2 \cdot 9 =\]
\[= \left( x^{2} + y^{2} \right)^{2} - 18 =\]
\[= \left( x^{2} + y^{2} + 2xy - 2xy \right)^{2} - 18 =\]
\[= \left( x^{2} + y^{2} + 2xy - 2 \cdot ( - 3) \right)^{2} - 18 =\]
\[= \left( (x + y)^{2} + 6 \right)^{2} - 18 =\]
\[= \left( 6^{2} + 6 \right)^{2} - 18 =\]
\[= (36 + 6)^{2} - 18 = 42^{2} - 18 =\]
\[= 1764 - 18 = 1746\]